An historical view of the experimental leptospiral infection in ruminants. (December 2020) - Rocha, Bruno Ribeiro; Martins, Gabriel; Lilenbaum, Walter
Highlights: Pregnant animals were more likely to present acute signs mainly by incidental infections. Chronic genital infection process and its consequences remains to be elucidated. There was observed a lack of standardization of techniques was compromised the outcomes. Bovine genital leptospirosis is a new disease and should be explored by experimental studies. Abstract: The first experimental infections with Leptospira in ruminants were conducted in the 1950s, primarily assessed the pathogenesis caused by serovar Pomona in cows. Throughout the decades, experimental infections have also demonstrated the clinical aspects of the infection by other strains, mainly Hardjo. Despite the important outcomes observed in experimental infections in ruminants, there is still a large discrepancy regarding the ideal dose, route, strain, model species or animal age that should be used to reproduce the acute and chronic leptospirosis in ruminants. In this context, the present study aimed to review the historical processes involved on the experimental leptospiral infection in ruminants. The inclusion criteria were papers that clearly described inoculation route, strain, dose, clinical signs and animal age. Overall, 37 experiments were noted. The most frequently reported clinical signs were fever, prostration, hematuria and death, with the majority of them occurring in young animals infected by incidental strains. Regarding reproductive problems, they occurred in the majority of the experiments and were also more related to incidental strains. In this context, abortions, retained placenta and weak fetuses were the most frequent symptoms. Noteworthy that although the mechanisms of the clinical acute disease either systemic or reproductive, is reasonably well understood, the physiopathology involved on reproductive problems due to the silent chronic infection is less discussed and remains to be elucidated. In this context, it is evident the need for studies focused on the genital infection and reproductive aspects of leptospiral infection in ruminants.